Groundwork for Political Negotiation in South Africa - Hendrik van der Merwe (Communicare)
This paper was presented to the symposium on The Communication Process of Political Negotiations at the Randse Afrikaanse Universiteit on 12 August 1988. It was condensed from the forthcoming book Pursuing Justice and Peace in South Africa, published by Routledge in London. The author grate fully acknowledges financial support from the Human Sciences Research Council In the form of a senior resaerch grant for study abroad. Opinions expressed or conclusions arrived at are those of the author, and are not to be regarded as those of the Human Sciences Research Council.